ENAM mutations and digenic inheritance. Issue 10 (2nd September 2019) - Zhang, Hong; Hu, Yuanyuan; Seymen, Figen; Koruyucu, Mine; Kasimoglu, Yelda; Wang, Shih‐Kai; Wright, John Timothy; Havel, Michael W.; Zhang, Chuhua; Kim, Jung‐Wook; Simmer, James P.; Hu, Jan C.‐C.
Abstract: Background: ENAM mutations cause autosomal dominant or recessive amelogenesis imperfecta (AI) and show a dose effect: enamel malformations are more severe or only penetrant when both ENAM alleles are defective. Methods: Whole exome sequences of recruited AI probands were initially screened for mutations in known AI candidate genes. Sanger sequencing was used to confirm sequence variations and their segregation with the disease phenotype. The co‐occurrence of ENAM and LAMA3 mutations in one family raised the possibility of digenic inheritance. Enamel formed in Enam +/+ Ambn +/+, Enam +/−, Ambn +/−, and Enam +/− Ambn +/− mice was characterized by dissection and backscattered scanning electron microscopy (bSEM). Results: ENAM mutations segregating with AI in five families were identified. Two novel ENAM frameshift mutations were identified. A single‐nucleotide duplication (c.395dupA/p.Pro133Alafs*13) replaced amino acids 133‐1142 with a 12 amino acid (ATTKAAFEAAIT*) sequence, and a single‐nucleotide deletion (c.2763delT/p.Asp921Glufs*32) replaced amino acids 921‐1142 with 31 amino acids (ESSPQQASYQAKETAQRRGKAKTLLEMMCPR*). Three families were heterozygous for a previously reported single‐nucleotide ENAM deletion (c.588+1delG/p.Asn197Ilefs*81). One of these families also harbored a heterozygous LAMA3 mutation (c.1559G>A/p.Cys520Tyr) that cosegregated with both the AI phenotype and the ENAM mutation. In mice, Ambn +/− maxillary incisors were normal. Ambn +/− molars were also normal, except for minor surface roughness. Ambn +/− mandibular incisors were sometimes chalky and showed minor chipping. Enam +/− incisor enamel was thinner than normal with ectopic mineral deposited laterally. Enam +/− molars were sometimes chalky and rough surfaced. Enam +/− Ambn +/− enamel was thin and rough, in part due to ectopic mineralization, but also underwent accelerated attrition. Conclusion: Novel ENAM mutations causing AI were identified, raising to 22 the number of ENAM variations known to cause AI. The severity of the enamel phenotype in Enam +/− Ambn +/− double heterozygous mice is caused by composite digenic effects. Digenic inheritance should be explored as a cause of AI in humans. Abstract : We report ENAM mutations segregating with a hypoplastic amelogenesis imperfecta (AI) phenotype in five families. The co‐occurrence of ENAM and LAMA3 mutations in one family (both genes are candidate genes for amelogenesis imperfecta) raised the possibility of digenic inheritance. Using Enam and Ambn knockout models we demonstrate digenic effects can increase the severity of enamel malformations.